The life of U’s: Order revisions on NASDAQ - Nikolsko-Rzhevska, Olena; Nikolsko-Rzhevskyy, Alex; Black, Jeffrey R. (Journal of Banking & Finance, 2020)
By recovering data on individual revision “U”-messages on NASDAQ, this paper is the first to reconstruct and then examine chains of order revisions. In recent years, revisions have grown in popularity and now are thrice as common as executions. The research on revisions, however, is still developing. We find significant differences between the determinants of revisions and cancellations/placements as order updating techniques. Our results also indicate that traders appear to respond rationally to new information by updating their orders based on order flow. We also show that revision runs follow stable, predictable patterns. Additionally, we find evidence suggesting increased revision activity has deleterious effects on market quality.